2017
DOI: 10.1111/jbi.12986
|View full text |Cite
|
Sign up to set email alerts
|

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography

Abstract: Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography, by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon‐scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well‐established methodology of horizon scanning to identify priority research questions in isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
211
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 192 publications
(217 citation statements)
references
References 192 publications
(244 reference statements)
2
211
1
3
Order By: Relevance
“…In fact, several important ideas in island biology, such as 'relaxation' (Brown 1971) and 'rescue effect' (Brown and Kodric-Brown 1977), derive from research on ILS. How patterns and processes of biological diversity compare across insular systems (true islands and ILS), has recently been identified as one of the 50 fundamental open questions in island biology (Q3 in Patiño et al 2017) and is of high importance to the field. in the 'Encyclopedia of islands'; Gillespie and Clague 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several important ideas in island biology, such as 'relaxation' (Brown 1971) and 'rescue effect' (Brown and Kodric-Brown 1977), derive from research on ILS. How patterns and processes of biological diversity compare across insular systems (true islands and ILS), has recently been identified as one of the 50 fundamental open questions in island biology (Q3 in Patiño et al 2017) and is of high importance to the field. in the 'Encyclopedia of islands'; Gillespie and Clague 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Kueffer et al 2014b;Borges et al 2016a;Patiño et al 2017) and montane environments (Huber et al 2006) to answer global questions about biodiversity, environmental change and sustainability (see Appendix S1 for a more detailed list of initiatives).…”
Section: Introductionmentioning
confidence: 99%
“…Exactly fifty years ago Robert MacArthur and Edward O. Wilson, in their seminal publication titled 'The Theory of Island Biogeography '(1967), introduced a general mathematical theory to predict the species richness of an island (or an isolated habitat), based on such factors as the rates of immigration and extinction determined by the size of the island and its distance from the mainland. They inferred that the island area and isolation eventually reach a dynamic equilibrium which they referred to as 'the equilibrium model of island biogeography Wilson, 1963, 1967;Patino et al 2017). They showed that the extent of decline in bird faunas distributed across the archipelagos of Melanesia, Micronesia and Polynesia, progressively increased from islands near to the mainland of New Guinea to intermediate and far islands (up to distance >3,200 km from the mainland) owing to their increasing geographical isolation, exhibiting typical island syndromes.…”
Section: Theory Of Island Biogeography Fifty Years Onmentioning
confidence: 99%
“…Fifty years on from its publication, MacArthur and Wilson's (1967) book remains one of the most influential texts on ecology and evolution, and continue to be a springboard for research on the origin and maintenance of biological communities. Coinciding with the 50 th anniversary of the publication of this landmark publication, Patino et al (2017) developed a roadmap for research on island biology. It identifies 50 fundamental questions in four key research foci through a collaborative horizon-scanning approach among the biogeographic community.…”
Section: Paradigm Shift In Biogeographymentioning
confidence: 99%